Peningkatan Literasi Keuangan melalui Pendampingan Penyusunan Laporan Keuangan SAK EMKM pada UMKM Uberrr - Indah Permata Suryani; Jefril Rahmadhoni; Cesar Welya Refdi; Ismed Ismed; Felga Zulfia Rasdiana; Risti Kurnia Dewi; Viska Rahma Puspita; Dian Ferinda (Warta Pengabdian Andalas, 2023)
MSMEs are one aspect that significantly contributes to the Indonesian economy; most MSMEs have minimum capacity knowledge of the importance of preparing financial reports according to accounting standards. Even though this understanding is essential to review business development and financial transparency, most MSMEs do not maximise their usefulness. In order to provide knowledge to MSMEs about recording financial reports, community service was carried out through mentoring and training to one of the MSMEs in Solok City, namely the Uberrr MSME. The method used was Adaptive Collaboration Management (ACM) by conducting training led by an expert in accounting and finance in preparing financial reports by financial accounting standards for Micro, Small and Medium Enterprises criteria, namely SAK EMKM. It increased the capacity of Uberrr's MSMEs in making simple bookkeeping and compliance with financial records. Further, it can increase MSME business owners' understanding of the importance of recording financial reports by accounting standards. This community service was a form of collaborative training between the government of Solok City and the Universitas Andalas Matching Fund Team.